2020
DOI: 10.3390/molecules25092011
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Antibacterial Activity of Aronia melanocarpa (Michx.) Elliot, Cornus mas L. and Chaenomeles superba Lindl. Leaf Extracts

Abstract: The purpose of this study was to investigate the composition of leaf extracts from Aronia melanocarpa, Chaenomeles superba, and Cornus mas, and their antimicrobial activity against typical spoilage-causing and pathogenic bacteria found in meat and meat products. The highest total phenolic content (TPC) was detected in C. superba extract, followed by C. mas and A. melanocarpa extracts. The antioxidant capacity of the extracts was measured by DPPH and ABTS assays. The lowest IC50 values were found for C. superba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 68 publications
(82 reference statements)
3
49
0
1
Order By: Relevance
“…Ellagitannins 8 and 10 , provided [M − 2H] −2 at m/z = 708.0688 and [M − H] − at m/z = 1417.1549, which were identified as two anomers or other isomers of camptothin A, a dimer in which gemin D and isocoriariin F constitute monomers [ 30 , 33 ]. Compounds 17 , 23 , 24 , 25, and 28 gave two ions, [M − 2H] −2 at m / z = 784.0729 and [M − H] − at m/z = 1569.1556, which indicated five isomers of galloyl-camptothin A known as cornusiin A [ 29 , 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ellagitannins 8 and 10 , provided [M − 2H] −2 at m/z = 708.0688 and [M − H] − at m/z = 1417.1549, which were identified as two anomers or other isomers of camptothin A, a dimer in which gemin D and isocoriariin F constitute monomers [ 30 , 33 ]. Compounds 17 , 23 , 24 , 25, and 28 gave two ions, [M − 2H] −2 at m / z = 784.0729 and [M − H] − at m/z = 1569.1556, which indicated five isomers of galloyl-camptothin A known as cornusiin A [ 29 , 31 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ellagitannins 8 and 10 , provided [M − 2H] −2 at m/z = 708.0688 and [M − H] − at m/z = 1417.1549, which were identified as two anomers or other isomers of camptothin A, a dimer in which gemin D and isocoriariin F constitute monomers [ 30 , 33 ]. Compounds 17 , 23 , 24 , 25, and 28 gave two ions, [M − 2H] −2 at m / z = 784.0729 and [M − H] − at m/z = 1569.1556, which indicated five isomers of galloyl-camptothin A known as cornusiin A [ 29 , 31 , 33 ]. In addition, two isomers of cornusiin A ( 17 , 23 ) fragmented to the ion at m / z 1417, after the loss of galloyl, but all its isomers detached a fragment of monomeric ellagitannins such as gemin D (at m / z 633) and tellimagrandin I (at m / z 785), which indicated that the compound consisted of these structures, as well as a fragment (at m / z 783) of oenothein C or dehydrated isocoriariin F (from 802 − 18 = 784) [ 26 , 29 , 31 ], the ion at m / z 935 corresponding to the fragment formed after loss of HHDP, galloyl, and glucose (e.g., gemin D).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations